Do the age profiles of health care expenditure really steepen over time? New evidence from Swiss cantons - Stefan Felder; Andreas Werblow (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
The red herring hypothesis contends that the high health care expenditure in old age is caused by proximity to death rather than calendar age. Dissenters point to longitudinal data and claim that health care expenditure age profiles tend to steepen over time. The present paper tests the steepening claim for Swiss health insurance, covering the time period 1997 to 2006 and 25 cantons. It analyzes the cantonal health care expenditure profile of men and women, taking into account differences in the mortality rates. The study covers seven components of health care, including long-term care. By and large, no evidence is found for relevant steepening effects of age profiles for either total, or the components, of health care expenditure.
Keywords: I12; J14; 330; Ageing; health care expenditure; end-of-life expenditure; Gesundheitskosten; Alternde Bevölkerung; Sterblichkeit; Schätzung; Schweiz